Model‐based clinical pharmacology profiling of ipilimumab in patients with advanced melanoma. (July 2014) - Feng, Yan; Masson, Eric; Dai, David; Parker, Susan M.; Berman, David; Roy, Amit
<x xml:space="preserve">Abstract</x> Aim Ipilimumab is a fully human, monoclonal antibody that blocks cytotoxic T‐lymphocyte antigen‐4. The objective of the present study was to characterize the clinical pharmacology profile of ipilimumab using a population pharmacokinetic (PPK) approach. Methods The PPK model was developed using 2095 ipilimumab serum concentration values from 499 patients with unresectable stage III or IV melanoma from four phase II studies, with ipilimumab doses ranging from 0.3 to 10 mg kg−1. The structural PK model was determined by developing a base PPK model. The effect of covariates on model parameters was assessed by a full covariate model, which incorporated all pre‐specified covariate‐parameter relationships into the base model. The final model was developed by backward elimination, followed by exclusion of covariates determined not to be of clinical relevance to ipilimumab, and was rigorously validated against both internal and external datasets. Results Ipilimumab PK was linear and time‐invariant, with dose‐proportional exposures over the available dose range, yielding a terminal half‐life of approximately 15 days. Clearance of ipilimumab increased with increasing body weight and baseline serum lactate dehydrogenase concentrations, but was not affected by age, gender, concomitant budesonide, Eastern Cooperative Oncology Group performance status or prior systemic anticancer therapy. Furthermore, ipilimumab exposure was not affected by moderate renal impairment or mild hepatic impairment. Conclusions Ipilimumab concentration–time data were well described by a linear, two compartment, zero order i.v. infusion model. The model confirms that a body weight‐normalized dosing regimen is appropriate for ipilimumab therapy in patients with advanced melanoma.